2015
DOI: 10.1186/s12985-015-0367-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of monoclonal antibodies and serological assays specific for Barley yellow dwarf virus GAV strain

Abstract: BackgroundBarley yellow dwarf virus (BYDV) is one of the most devastating plant viruses and belongs to a ubiquitous plant virus group. In China, four BYDV strains (GPV, GAV, PAV and RMV) have been identified based on their specific aphid vectors and serological properties. Among the four identified strains, the GAV is the most common BYDV strain in China. To diagnose, forecast of BYDV GAV, two reliable serological assays for BYDV GAV detection were established.MethodsWe purified virion from a confirmed BYDV GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The positive detection of the MP with anti-MP antisera may indicate that the virus is in the multiplication stage. Polyclonal and monoclonal MP antibodies specific to Barley yellow dwarf virus (Xie et al 2007;Li et al 2015), polyclonal MP antibody specific to Citrus leprosis virus C (Calegario et al 2012), and polyclonal MP antibody specific to Grapevine fanleaf virus (Koolivand et al 2016) have been reported to detect the corresponding viruses, but most were effective only in laboratory use. Western blotting with anti-MP PLRV in our study showed that the antiserum could detect PLRV efficiently, although ratios of 1:10000 to 1:40000 were better for color development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive detection of the MP with anti-MP antisera may indicate that the virus is in the multiplication stage. Polyclonal and monoclonal MP antibodies specific to Barley yellow dwarf virus (Xie et al 2007;Li et al 2015), polyclonal MP antibody specific to Citrus leprosis virus C (Calegario et al 2012), and polyclonal MP antibody specific to Grapevine fanleaf virus (Koolivand et al 2016) have been reported to detect the corresponding viruses, but most were effective only in laboratory use. Western blotting with anti-MP PLRV in our study showed that the antiserum could detect PLRV efficiently, although ratios of 1:10000 to 1:40000 were better for color development.…”
Section: Discussionmentioning
confidence: 99%
“…Most plant viruses contain MP genes in their genome that are associated with cell-to-cell movement of the virus through the plasmodesmata (Wolf et al 1989;Haupt et al 2005;Akamatsu et al 2007). Anti-MP antisera used to detect these MPs in different plant viruses have been reported (Xie et al 2007;Calegario et al 2012;Li et al 2015;Koolivand et al 2016). As far as we know, there is no report on the preparation of PLRV-MP antiserum used for the detection of PLRV and its MP.…”
Section: Introductionmentioning
confidence: 99%
“…After the forth immunization, spleen cells were obtained from the immunized mice and used to produce hybridoma as described (Liu et al 2016). Screening of hybridomas secreting anti-WDV MAbs and production of ascitic fluids were as described by Li et al (2015). Specificity of the resulting MAbs was determined by Western blot as described previously (Wu et al 2013).…”
Section: Preparation Of Mabsmentioning
confidence: 99%
“…To date, several WDV detection methods, including a squash blot (Bendahmane 1995), PCR or Real-time PCR (Achon et al 2006;Koklu et al 2007;Zhang et al 2010), nucleic acid spot hybridization (NASH) (Jin et al 2015), and a polyclonal antibody (PAb)-based enzyme-linked immunosorbent assay (ELISA) (Nygren et al 2015), have been reported. Compared with PCR, realtime PCR and nucleic acid spot hybridization, serological assays were considered to be more convenient assays for large-scale epidemiological studies and on-site detection of viruses during field surveys (Li et al 2015;Liu et al 2016;Chen et al 2017). It is generally accepted that a reliable serological detection assay depends largely on the specificity and sensitivity of the antibody used in the assay.…”
Section: Introductionmentioning
confidence: 99%
“…In regards to the serological detection, only antiserum against CABYV prepared by purified virion was once used in Western blotting or ELISA [4]. Some recent studies showed that polyclonal antiserum against MP can detect the accumulation of virus from the family Luteoviridae [40][41][42][43]. However, there are no reports on either preparing polyclonal antiserum against MP of the three viruses or the serological relationships among them.…”
Section: Introductionmentioning
confidence: 99%